Complications of thrombolysis in an intensive care unit - Deimantavičienė, Živilė; Klimas, Nerijus; Pečkauskas, Aurimas; Bakšytė, Giedrė; Macas, Andrius; Pieteris, Linas; Repšienė, Aurelija (Acta medica Lituanica, 2012)
Background. Thrombolysis is often the only way in treating people with life-threatening conditions, like acute myocardial infarction (AMI), pulmonary embolism (PE) and acute ischemic stroke (AIS). Complications of thrombolytic therapy are not rare and have clear influence in the quality of life, hospital stay, outcomes and mortality. Most common complications are intracranial hemorrhage, severe injection site, nose, vaginal bleeding and peripheral hematomas. Methods and materials. A retrospective study took place in the Department of Intensive Care, Hospital of Lithuanian University of Health Sciences Kaunas Clinics. Medical data of 83 patients, who underwent treatment with thrombolytic drugs in the period of 2007–2011, were analyzed. All patients were treated with intravenous infusion of Alteplase. Inclusion criteria were as follows: • AMI, AIS or PE treatable with thrombolytic therapy. Results. 72.3% (n = 60) of patients experienced massive PE, 13.3% (n  =  11) AMI and 14.4% (n  =  12) AIS. There were 8.43% (n  =  7) of patients who had bleeding complications – 2.4% (n = 2) experienced nose bleed during or shortly after thrombolytic therapy, 3.6% (n = 3) had injection site bleeding and 1.2% (n = 1) experienced multiple skin hemorrhages. 11.7% (n = 7) of patients in the group of massive PE were thrombolised during CPR and only one of them experienced bleeding to the pleural cavity. There were no internal or external bleeding observed neither in AMI nor in AIS groups. In-hospital mortality after thrombolytic therapy was 20.5% (n = 17). Conclusions. Thrombolytic therapy very often is the only way in treating acute, life-threatening diseases, like acute myocardial infarction, pulmonary embolism or acute ischemic stroke. Intracranial hemorrhage, injection site, nose, vaginal bleeding and peripheral hematomas are the most common complications of thrombolysis. Risk factors should be evaluated before starting the thrombolytic therapy. Data of our hospital experience do not dramatically differ from worldwide data.
Keywords: Alteplase; thrombolysis; complications; intensive care unit; thrombolytic therapy